Weak Form Efficient Market Hypothesis and January Effect; Study Case in LQ45 Index of Indonesia Stock Exchange Market Period 2016-2018 - B12112012, Angelia Kholesta Kholesta (Jurnal Manajemen Update, 2019)
ABSTRACT The purpose of this research to test and analyze whether Weak Form Efficient Market Hypothesis and January Effect exist in LQ45 Index of Indonesia Stock Exchange Market 2016-2018 or not. This research is quantitative research which is using the Run test and One Way Anova test. The data collection methods of this research are by collecting the data of stock price of the market of LQ45 from yahoo finance.Based on the results of the test of this paper, it can be concluded that Weak Form Efficient Market exists in LQ 45 Index of LQ45 while for the January Effect are not found to exist in LQ 45 Index of LQ45. In conclusion, it is observed that the effect of stock prices for the sample companies on future prices is very meager and an investor cannot gain optimal profits by using the historical share price data as the current share prices already reflect the effect of past share prices data. Keywords: Efficient Market Hypothesis, LQ45 Indonesia Stock Exchange Market, non-parametric test, parametric test.  REFERENCE Abraham, a. I. (1994). The Individual Investor and the Weekend Effect . Journal of Financial and Quantitative Analysis, Vol 29, 263-277.Alexander, W. S. (1995). Investments, Fifth Edition. New Jersey: Prentice Hall.Algifari. (1999). Pengaruh Hari Perdagangan terhadap Return Saham di BEJ, Tesis UGM. Yogyakarta: UGM.Al-Ississ, M. (2010). The Impact of religious experience on financial markets. Working Paper, Harvard University.all, B. e. (2006). Investasi, Alih Bahasa oleh Alih Bahasa oleh Zuliani Dalimunthe dan Budi Wibowo. Jakarta: Salemba Empat.Ang, R. (1997). Buku Pintar Pasar Modal Indonesia. Jakarta: Mediasoft Indonesia.Anoraga, P. a. (2006). Pengantar Pasar Modal Edisi Revisi. Jakarta: Rineka Cipta.As'adah, L. (2009). Pengaruh January Effect terhadap Abnormal Return dan Volume Perdagangan Pada Saham di Jakarta Islamic Center (JII). Skripsi, Fakultas Syari'ah Universitas Islam Negeri Sunan Kalijaga, Yogyakarta.Balaban, E. A. (2001). Stock Return Seasonality and Asymmetric Conditional Volatility in World Equity Markets. Applied Economics Letters, 8(4), 263-268.Ball, R. (2009). The Global Financial Crisis and The Efficient Makret Hypothesis; What Have We Learned? Journal of Applied Corporate Finance, 21(4), 8-16.Barro, R. J., & McCleary, R. M. (2003). Religion and economics growth across countries. American Sociological Review, 68(5), 760-781.Basu, S. (1977). Investment Performance of Common Stocks in Relation to Their Price - Earnings Ratios : A Test of the Efficient Market Hypothesis. Journal of Finance Vol 32, Issue 3, 663 - 82.Beit-Hallahmi, B. A. (1997). The psychology of religious behavior : Belief and experience. London: Routledge.Bialkowski, J., Etebari, A., & Wisniewski, T. P. (2012). Fast profits: Investor sentiment and stock returns during Ramadan. Journal of Banking & Finance, 36, 835-845.Brav, A., & Heaton, J. B. (2002 ). Competing Theories of Financial Anomalies. Review of Financial Studies, 15(2), 575.Britama.com. (2017, July 24). Daftar Saham Indeks LQ 45 Periode Agustus 2017 - Januari 2018. Retrieved June 25, 2019, from Britama.com: https://britama.com/index.php/2017/07/daftar-saham-indeks-lq-45-periode-agustus-2017-januari-2018/Cadsby, C. B. (1992). Turn-of-month and pre-holiday effects on stock returns: Some international evidence. Journal of Banking and Finance, 16(3), 497-509.Cahyowati, M. J. (2015). Analisis January Effect Dengan Menggunakan Metode GARCH pada Bursa Saham Indonesia, Malaysia dan Singapura Periode 1999-2013. Yogyakarta: Universitas Atma Jaya Yogyakarta.Cahyowati, M. J. (2015). ANALISIS JANUARY EFFECT DENGAN MENGGUNAKAN METODE GARCH PADA BURSA SAHAM INDONESIA, MALAYSIA, DAN SINGAPURA PERIODE 1999-2013.Chatterjee, A. (2000). Market Anomalies Revisited. Journal of Applied Business Research, Vol : 13 No. 4.Chaudhry, R.-D. a. (2000). January Anomalis: Implications for the Market's Incorporation of News. The Financial Review, Vol : 3, 79-96.Chotigeat T., P. I. (2005). Seasonality in Asia's Emerging Markets: India and Malaysia. International Trade and Finance Association, 53.Coki. (n.d.). Keuntungan dan Kerugian dalam investasi saham. Retrieved May 06, 2018, from Capital Market Education's by Coki: https://coki002.wordpress.com/keuntungan-dan-kerugian-dalam-investasi-saham/Cross, F. (1973). The Behaviour of Stock Price on Friday and Monday. Financial Analysis Journal, Vol. 29, 67-69.D.N, S. W. (2012). Anomali Pasar pada Return Saham : The Day of The Week Effect, Week Four Effect, Rogalsky Effect dan January Effect, Vol. 2, No. 1. Jurnal Ilmiah Akuntansi dan Humanika JINAH.D.S, S. (2011). Existence of Certain Anomalies In Indian Stock Market, Proceedings of International Conference on Economic and Finance Research. School of Social Science VIT University.Dajan, A. (1996). Pengantar Metode Statistik Jilid II. Jakarta: LP3S.Darmadji, T. a. (2012). Pasar Modal di Indonesia Edisi Ketiga. Jakarta: Salemba Empat.Daswan, A. d. (2011). January Effect pada Perusahaan LQ 45 Bursa Efek Indonesia 2003-2008. Jurnal Ekonomi,19(3).Deannes, P. C. (2015, April 1). January Effect Pada Perusahaan LQ 45 di Bursa Efek Indonesia Periode 2009-2013. e-Proceeding of Management : Vol.2, 524.Delfeld, C. (2016, May 25). foreign investing vietnam. Retrieved August 24, 2017, from wallstreetdaily: https://www.wallstreetdaily.com/2016/05/25/foreign-investing-vietnam/Dina, A., & Herman, H. (2007). Pengujian January Effect di Bursa Efek Jakarta (Studi Kasus Perusahaan LQ45 di BEJ).Downes, J. G. (2004). Kamus Istilah Keuangan dan Investasi Edisi 3. Jakarta: PT. Elex Media Komputindo.Dubois . M, a. L. (1996). The day of the week effect : The International Evidence. Journal of Banking and Finance, 20(9), 1463-84.Ekonomi, S. (2018, Februari 03). Manfaat dan Fungsi Indeks Harga Saham. Retrieved Juli 12, 2018, from Sudut Ekonomi: https://sudutekonomi.blogspot.com/2018/02/manfaat-dan-fungsi-indeks-harga-saham.htmlErickson, L. W. (1997). A New Look At the Monday Effect. Journal of Finance, Vol: 52, 2171-2186.Fakhruddin, D. a. (2001). Pasar Modal di Indonesia. Jakarta: Salemba Empat.Fama, E. (1970). Efficient Capital Markets : A Review of Theory and Empirical work. American Finance Association, 25(2), 383-417.Fama, E. F. (1970). Efficient Capital Markets: a Review of Theory and Empirical Work. The Journal of Finance, Vol. 25, Issue 2, pp 383-417.Fama, E. F. (1970). Efficient Captial Market: a Review of Theory and Empirical Work.The Journal of Finance, Vol. 25, Issue 2, pp 383-417.Fauzi, N. (2007). Analisis Fenomena Anomali Pasar January Effect dan Korelasi di antara Tiga Emerging Stock Market Asia Periode 2000-2006. Jurnal Akuntansi dan Manajemen,2(2), 63-77.Finance, D. (2013, January 18). January Effect, 'Tamu' Pasar Modal Tiap Awal Tahun. Retrieved May 15, 2018, from https://finance.detik.com/portofolio/d-2145847/january-effect-tamu-pasar-modal-tiap-awal-tahunGusvianto, R. (2015). WEAK FORM EFFICIENT MARKET HYPOTHESIS AND CALENDAR EFFECT IN LQ 45 INDEX OF INDONESIA STOCK EXCHANGE MARKET IN 2009-2014. Pontianak: Universitas Tanjungpura.Hadi Wijaya, D. A. (2014). Analisis January Effect Pada Sektor Manufaktur di Bursa Efek Indonesia (BEI). STIE MDP.Hadi, I. F. (2009). Teori Portofolio dan Analisis INvestasi . Bandung: Alfabeta.Hartono, M. J. (2010). Teori Portofolio dan Analisis Investasi Edisi Ketujuh. Yogyakarta: BPFE UGM.Hendi, T. D. (2001). Pasar Modal di Indonesia: Pendekatan Tanya Jawab, Edisi Pertama . Jakarta: Salemba Empat.Hermawan, S. d. (Desember 2001). Pengujian January Effect Terhadap Return Saham Sektor Manufaktur : Pengujian Pada 15 saham Perusahaan Kecil dan 15 Perusahaan Besar di Bursa Efek Jakarta Tahun 1996-2000. Jurnal Penelitian Ekonomi, Bisnis, dan Pembangunan, Empirika No 2, 183-204.Imam, A. (2009). Analisis Anomali Pasar Efisien Pada Bursa Efek Indonesia (Studi Kasus Saham-Saham Jakarta Islamic Index).Indah Fitriyani, M. M. (2013). Analisis January Effect Pada Kelompok Saham Indeks LQ 45 di BEI Tahun 2009-2011. E-Jurnal Akuntansi Universitas Udayana 4.2 , 421 - 438.Iramani, R. M., & Mahdi, A. (2006). Studi Tentang Pengaruh Hari Perdagangan Terhadap Return Saham Pada BEJ. Jurnal Akuntansi dan Keungan, Vol 8 No.2:63-70.J Bialkowski, A. E. (2012). Fast Profits: Investor Sentiment and Stock Returns During Ramadan. Journal of Banking & Finance 36, 835-845.Jaffe, J. y. (1985). The week-end effect in common stock returns: The International Evidence . Journal of Finance, 40(2), 433-454.Jogiyanto, H. (2005). Teori Portofolio dan Analisis Investasi, Edisi 7. Yogyakarta: BPFE.Jorion, H. R. (1966). The January Effect: Still There after II These Years. Financial Analyst Journal Vol:52:27-31.Keim. (1983). Size - Related Anomalies and Stock Return Seasonality: Further Empirical Evidence. Journal of Financial Economics.Kinney, M. &. (1976). Capital Market Seasonality: The case of stock return. Journal of Financial Economics, 3(4), 379-402.Kiymaz.H, H. a. (2001). The day of the week effect on stock market volatility. Journal of Economics and Finance 25(2), 181-190.Kohers, R. K. (1992). The Yearend Effect in Stock Returns Over Business Cycles: A Technical Note. Journal of Economics and Finance, 61-68.Kohli, T. K. (1991). The Anomalous Stock Market Behavior of Large Firms in January : The Evidence from the S&P Composite and Component Indexes. Quarterly Journal of Business and Economics, Summer, pp. 14 -32.Kumar, A., Page, J. K., & Spalt, O. G. (2011). Religious beliefs, gambling attitudes and financial market outcomes. Journal of Financial Economics, 102(3), 671-708.Lakonishok, J. &. (1988). Are seasonal anomalies real? A ninety-year perspective. Review of Financial Studies, 1(4), 403-425.Levy, B. I. (Spring 1997). High-Definition Style Rotation. The Journal of Investing and Abstracted in The CFA Digest.Maberly, E. (1995). Eureka! Eureka! Discovery of the Weekend Effect Belongs to the Ancient Scribes. Financial Analysis Journal, 10-11.MAČERINSKIENĖ, I., & Kartašova, J. (June 17-20 2012). Calender Anomalies in the Lithuanian Stock Market? Scientific Proceedings :Conference Proceedings Volume II : Jubilee X International Scientific Conference . Sozopol, Bulgaria: Management and Engineering'12.MacKinlay, A. C. (1997). Event Studies in Economics and Finance. Journal of Economic Literature, 35 : 13-39.Mahdi, I. d. (2006). Studi Tentang Pengaruh Hari Perdagangan Terhadap Return Saham pada BEJ. Jurnal Akuntansi dan Keuangan, 8(2), 63-70.Malkiel, B. G., & E. F. Fama. (1970). Efficient capital markets : A review of theory and empirical work. The Journal of Finance 25(2), 479-513.McColl, E. a. (1997). Statistics Glossary V1.1.Michael S. Rozeff and Willian R. Kinney, J. (1976). Capital Market Seasonality : The Case of Stock Returns. Journal of Financial Economics, Vol 3, No. 4 (October), 379 - 402.Mishkin, F. S., & Eakins, S. G. (2012). Financial Markets and Institutions Prentice Hall Finance Series. Prentice Hall.Munadi, A. (2013). Ramadhan Effect : Pengaruh Bulan Ramadhan Terhadap Pergerakan Harga Saham di Indonesia. Skripsi Sarjana Fakultas Ekonomika dan Bisnis Universitas Gadjah Mada.Nagastara, A. a. (2012). Analysis of January Effect in Indonesian Bangking Sector During the Period of 2005-2012. European Journal of Economic, Finance and Administrative Sciences, 49.Nagastara, A. d. (2012). Analysis of January Effect in Indonesia Banking Sector During the Period of 2005-2012. European Journal of Econimic, Finance and Administrative Sciences, Issue 49.Nasruldin. (2011). Pengujian Hipotesis Pasar Efisien Bentuk Lemah Pasar Modal Indonesia Periode 2009-2010 (Studi Kasus pada Perusahaan yang Terdaftar dalam Indeks LQ 45).OK, S. (2015, August 23). Saham LQ 45 2014 Agustus - 2015 Januari. Retrieved June 25, 2019, from Saham Ok: https://www.sahamok.com/bei/lq-45/saham-lq-45-2014-agustus-2015-januari/ok, S. (n.d.). Saham LQ 45 2015 Agustus - 2016 Januari. Retrieved June 25, 2019, from Saham Ok: https://www.sahamok.com/bei/lq-45/saham-lq-45-2015-agustus-2016-januari/Ok, S. (n.d.). Saham LQ 45 2015 Februari - Juli. Retrieved June 25, 2019, from Saham Ok: https://www.sahamok.com/bei/lq-45/saham-lq-45-2015-februari-juli/Ok, S. (n.d.). Saham LQ 45 Agustus 2016 - Januari 2017. Retrieved June 25, 2019, from Saham Ok: https://www.sahamok.com/bei/lq-45/saham-lq-45-agustus-2016-januari-2017/Ok, S. (n.d.). Saham LQ 45 Februari - Juli 2017. Retrieved June 25, 2019, from Saham Ok: https://www.sahamok.com/bei/lq-45/saham-lq-45-februari-juli-2017/Perera, S. T. (2012). Day of the Week Effect of Stock Returns: Empirical Evidence From Colombo Stock Exchange. Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka.Putri Cahaya Pertiwi Deannes, I. S. (2015). January Effect On Corporate LQ 45 In Indonesia Stock Exchange Period 2009-2013. e-proceeding of Management : Vol 2, No.1 April 2015 , 524.Rahman, S. B. (1991). Dividen Perusahaan dan Efisiensi di Pasar Modal Jakarta. Management dan Usahawan Indonesia.Ranita, R. (1983). The anomalous stock market behavior of small firms in January. Journal of Financial Economics 12, June, 89 - 104.Reinganum, M. (1983). The Anomalous Stock Market Behavior of Small Firms in January: Empirical Tests for Tax-Loss Selling Effect. Journal of Financial Economics, 12, 89-104.Rendra, T. (2004). Analisis Fenomena Efek Januari di Bursa Efek Jakarta Periode 1997-2001 . Jurnal Bisnis dan Manajemen, 4(1), 1-17.Renneboog, L., & Spaenjers, C. (2012). Religion, economic attitudes and household finance. Oxford Economic Papers, 64(1), 103-127.Riswandi. (2009). Ilmu Komunikasi. Yogyakarta: Graha Ilmu.Rita, M. (2009). Pengaruh hari perdagangan terhadap return saham: Pengujian Day of the Week Effect, Week Four Effect, dan Rogalski Effect di BEI.Riyadi, S. (2015, January 29). Reserve Requirement. Retrieved June 12, 2018, from Dosen Perbanas: https://dosen.perbanas.id/reserve-requirement-rr/Rogalski R.J and Tinic, S. (1986). The January Size Effect: Anomaly or Risk Mismeasurement? Financial Analysts Journal, 42, 63-70.Rosen, H. S., & Wu, S. (2004). Portfolio choice and health status. Journal of Financial Economics, 72(3), 457-484.Rozeff M.S and W.R Kinnet, J. (1976). Capital Market Seasonality : The Case of Stock Returns. Journal of Financial Economics, 3, 379-402.Sanger, C. G. (1989). Firm Size and Turn-of-the-Year Effects in the OTC / NASDAQ Market. The Journal of Finance, Vol. XLIV No.(5).Santoso, E. (2010). Analisis January Effect dengan Metode GARCH Pada Bursa Efek Indonesia Periode 2004-2008. Skripsi, Fakultas Ekonomi Universitas Atma Jaya Yogyakarta (tidak dipublikasi).Sari, F. A., & Sisdyani, E. A. (2014). January Effect Analysis in Indonesia Capital Market. E-Jurnal Akuntansi Universitas Udayana.Setiawan, P. (2015, February 07). 10 Pengertian dan Definisi Investasi Menurut Ahli Ekonomi. Retrieved May 31, 2018, from Guru Pendidikan: http://www.gurupendidikan.co.id/10-pengertian-dan-devinisi-investasi-menurut-ahli-ekonomi/Seyyed, F., Abraham, A., & Al-Hajji, M. (2005). Seasonality in stock returns and volatility. The Ramadan Effect. Research in International Business and Finance, 19(3), 374-383.Sharpe, W. A. (1995). Inverstment, Fifth Edition. New Jersey: Prentice Hall.Sisdyani, F. A. (2014). Analisis January Effect di Pasar Modal Indonesia. E-Jurnal Akuntansi Universitas Udayana 6.2, 237-248.Sri Werastuti, D. N. (2012). Anomali Pasar pada Return Saham; THE DAY OF WEEK EFFECT, WEEK FOUR EFFECT, ROGALSKY EFFECT, DAN JANUARY EFFECT. Jurnal Ilmiah Akuntansi Edisi Desember, Vol 2, No 1.Stambaugh, D. K. (1984). A Further Investigation of the Weekend Effect in Stock Returns. Journal of Finance, Vol 39, 819-835.Subekti, I. (2005). Pengujian Anomali January Effect dan Overreaction Hypothesis di Bursa Efek Jakarta. Malang: Universitas Brawijaya Malang.Subekti, I. (2006). Pengujian Anomali January Effect dan Overreaction Hypothesis di Bursa Efek Jakarta. Jurnal Ekonomi dan Manajemen 7(1), 108-116.Sutrisno, E. (2009). Manajemen Sumber Daya Manusia Edisi Pertama. Jakarta: Kencana Prenada Media Group.Syahril Djaddang, A. M. (2014). Anomali Efisiensi Pasar Sebuah Studi Pengaruh Musiman / Calender di Bursa Efek Indonesia Emiten LQ 45 Tahun 2010 - 2012. Konferensi Ilmiah Akuntansi 1 IAIKAPd Wilayah Jakarta Banten.Tandelilin, E. (2001). Analisis Investasi dan Manajemen Portofolio Edisi Pertama. Yogyakarta: BPFE.Tandelilin, E. (2010). Portofolio dan Investasi : Teori dan Aplikasi. Yogyakarta: Kanisius.Tandon, A. A. (1994). Annomalies or Illusions? Evidence From Stock Market In Eighteen Countries. Journal of International Money and Finance V 13, 83-106.Wachtel, S. (1942). Certain Observations on Seasonal Movements in Stock Prices. The Journal of BUsiness of the University of Chicago, 15, 184-193.Weber, M. (1930). The Protestant Ethic and the Spirit of Capitalism. New York: Scribner's.Westerfield, J. J. (1985). The week-end effect in common stock returns: The international evidence. Journal of Finance, 40(2), 433-454.Wijaya, T. (2012). Cepat menguasai SPSS. Yogyakarta: Cahaya Atma Pustaka.Witiastuti, D. C. (2010). Analisis Monday Effect dan Rogalsky Effect di Bursa Efek Jakarta, Vol. 1, No. 2. Jurnal Dinamika Manajemen, 154-168.Wong, K. A. (1992). Day of the Week Effect: The Evidence from Developing Stock Market. Applied Financial Economics, 2(1), 49-56.Wong, K. a. (1999). Short-term Seasonalities On The Jakarta Stock Exchange. Review of Pasific Basin Financial Markets and Policies, 2(3), 375-398.Wong.K, a. K. (1999). Short-term Seasonalities On The Jakarta Stock Exchange. Review of Pacific Basin Financial Markets and Policies, 2(3), 375-398.Yong. (1993). Thin Capital Markets: A Study of Stock Market Efficiency of Malaysian Stocks.Yong, A. R. (2002). Analisis Investasi dan Teori Portofolio. Jakarta: Raja Grafindo.Yunita Anwar, M. S. (June 2009). The day of the week effects in Indonesia, Singapore and Malaysia Stock Market. Munich Personal RePEc Archive.